Uma leitura psicanalítica sobre a humilhação social na contemporaneidade - Searson, Maria Eduarda Hasselmann de Oliveira Lyrio (2010)
There are not many specific studies about social humiliation. However, a new interest in the theme, evidenced by studies, theses, thematic meetings and websites, as well as a noticeable increase in legislative measures, has appeared as a response to the deterioration of human relationships in recent times. From a psychoanalytical perspective, this study will try to contribute to this theme. To consider humiliation as the suffering of a sole subject and also of many people, is to understand humiliation as a social phenomenon, caused by the tension and contradiction of the inseparable relationship between the subject and society. This analysis aims to avoid the victimization of the humiliated, in order to investigate the relevant subjective, social and political aspects that cause the human being to put himself in this place of extreme suffering, making it difficult for him to swap from the position of object of jouissance of the Other to the position of a subject who desires